A Study on Loss and Gain Meaning in the English Translation of Conceptual Metaphors Denoting the Concept of " Relationship" in Tring Cong Son's Songs - Phan Thị Phương (2014)
Introduction - Literature review and theoretical background - Research design and methodology....